Performance management in Tuberculosis and Leprosy control programme in Oyo State, Nigeria, 2017 - Dania, Oluyinka Motunrayo (My University, 2017)
Performance management (PM) has been shown to improve organisational performance and tuberculosis case detection rate. Despite the utilisation of PM within the tuberculosis and leprosy control programme (TBLCP) in Nigeria, the country’s tuberculosis case detection rate is amongst the poorest globally. This research therefore aimed to examine the fidelity with which PM is being implemented within the TBLCP. A mixed method approach was adopted, where quantitative questionnaires and semi-structured interviews were conducted. Quantitative data was primarily analysed using summary statistics and differences were assessed using the Wilcoxon Sign Rank test. Thematic analysis of the qualitative data was done. TBLCP staffs are responsive to PM but adherence is poor in the standards setting and implementation component of the PM system. The major reasons for the identified gaps were lack of local stakeholder involvement, lack of budget implementation and inadequate human resources. Implementation strategies need to be developed to address the gaps in the early stages of the PM process. If the identified gaps can be bridged, PM implementation will be optimised.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Masters in Epidemiology (Implementation Science) Johannesburg, November 2017.
Keywords: Performance Management; Tuberculosis; Leprosy